Peer Counseling Islami sebagai Strategi BK dalam Membina Kemandirian dan Karakter Religius Peserta Didik MA Al-Mahdi Serang - Lilis Kholilah; Septi Gumiandari (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
At MA Al-Mahdi Serang, there are challenges in the form of psychological distance between students and guidance and counseling teachers, as well as the negative influence of peers in the digital era that threaten students' independence and religious character. Islamic peer counseling is an alternative guidance and counseling strategy to support students' psychological needs while strengthening their independence and religious character. This study aims to (1) analyze the implementation of Islamic peer counseling services, (2) determine their influence on student independence, (3) explore their contribution to fostering religious character, and (4) formulate an effective Islamic guidance and counseling service model at MA Al-Mahdi Serang. This study uses a qualitative approach with a case study design. The research informants were 13 people consisting of the principal who is also a guidance and counseling teacher, the vice principal for curriculum, subject teachers, and students. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed using thematic analysis. The results of the study indicate that: (1) the implementation of Islamic peer counseling is carried out through a peer counselor recruitment process based on the criteria of noble character and communication skills, as well as counseling skills training based on the values ​​of brotherhood and tabayyun; (2) Islamic peer counseling services have a positive influence on student independence, particularly in self-management and decision-making; (3) Islamic peer counseling contributes to the development of religious character through the internalization of the values ​​of honesty, responsibility, discipline in worship, and the culture of tawashau bil haqq; and (4) the formulation of an Islamic peer counseling model based on the values ​​of brotherhood as an adaptive and contextual guidance and counseling service in madrasas.